2020
DOI: 10.1177/2047487320904641
|View full text |Cite
|
Sign up to set email alerts
|

Association of short-term exposure to air pollution with myocardial infarction with and without obstructive coronary artery disease

Abstract: Background Air pollution including particulate matter with an aerodynamic diameter ≤2.5 µm (PM2.5) increases the risk of acute myocardial infarction. However, whether short-term exposure to PM2.5 triggers the onset of myocardial infarction with nonobstructive coronary arteries, compared with myocardial infarction with coronary artery disease, has not been elucidated. This study aimed to estimate the association between short-term exposure to PM2.5 and admission for acute myocardial infarction, myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Environmental factors could trigger ACS and other cardiovascular events through various mechanisms, including plaque rupture, acute thrombosis, 32 and altered autonomic control. 33 Despite an abundance of data linking exposure to air pollutants and the onset of cardiovascular events, 24 , 25 , 32 only a few published studies have assessed if a similar association with exposure to pollen grains exists. Interestingly, this relationship was examined within the general population, and no details were provided about the history of preexisting allergic diseases or the use of antiallergy medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors could trigger ACS and other cardiovascular events through various mechanisms, including plaque rupture, acute thrombosis, 32 and altered autonomic control. 33 Despite an abundance of data linking exposure to air pollutants and the onset of cardiovascular events, 24 , 25 , 32 only a few published studies have assessed if a similar association with exposure to pollen grains exists. Interestingly, this relationship was examined within the general population, and no details were provided about the history of preexisting allergic diseases or the use of antiallergy medications.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accord with the methodology used in previous studies that evaluated the association of exposure to environmental triggers, including air pollutants and subsequent health outcomes. 24 , 25 , 26 , 27 Grass pollen count was grouped into high (≥50 grains/m 3 ) and low count (<50 grains/m 3 ), 20 whereas total pollen count was grouped into tertiles. 21 …”
Section: Methodsmentioning
confidence: 99%
“…External factors may include reduced physical activity, which is limited by weather conditions, and shortened exposure to the sun, which directly reduces the production of vitamin D in our bodies, and also intensified air pollution [26,27]. A study conducted in Japan in 2020 showed seasonal variation in the incidence of myocardial infarction, with a peak in spring, associated with an increase in PM 2.5 in the spring period [28]. The winter season also changes our eating habits; the amount of sodium intake and fat-rich foods increases.…”
Section: Acs -Acute Coronary Syndrome Nstemi -Non-st-segment Elevation Myocardial Infarction or -Odds Ratio Sd -Standard Deviation Stemi mentioning
confidence: 99%
“…2013). There is increasing evidence that exposure to ambient air pollutants is associated with an increased incidence of AMI (Chen et al 2018, Ishii et al 2021, Liu et al 2021). However, most of these are studies on particulate matter and AMI incidence, with few involving ozone (O 3 ), particularly in developing countries, and inconsistent outcomes.…”
Section: Introductionmentioning
confidence: 99%